INVESTIGATING FIGURATIVE LANGUAGE IN "GHOST OF YOU" SONG LYRICS - Karima Najma Laila; Kurniawan, Yulius (Language Horizon: Journal of Language Studies, 2025)
This study aims to assess the metaphorical language employed in the song "Ghost of You" by 5 Seconds of Summer, focusing specifically on how linguistic aspects convey the themes of loss and desire. This research employs a qualitative methodology, with the lyrical analysis grounded in the figurative language framework established by Perrine (1969). The findings indicate that this song contains seven forms of figurative language: metaphor, simile, personification, metonymy, irony, symbol, and hyperbole. Each form of figurative language plays a crucial role in amplifying the emotional significance embedded in the lyrics. Hyperbole and metaphor illustrate the intensity of loss and longing, whilst symbolism and personification convey the enduring nature of memories. This study contributes to stylistic research by highlighting the significant significance of figurative language in augmenting the emotional resonance of a song.